Expression of cytotoxic T lymphocyte-associated antigen 4, CD44, and E-cadherin in the microenvironment of breast carcinomas - Bölme Şavlı, Tuğçe; Paşaoğlu, Hüsniye Esra; Şavlı, Taha Cumhan; Muhammedoğlu, Ali; Tokoçin, Merve; Öztürk, Çiğdem (NLM (Medline), 2023)
OBJECTIVE: The expression of cytotoxic T lymphocyte-associated antigen 4, E-cadherin, and CD44 in the area of tumor budding was investigated in breast carcinomas in our study. METHODS: Tumor budding was counted at the invasive margins in 179 breast carcinomas. To understand the microenvironment of tumor budding, we examined the expression status of the immune checkpoint molecules such as cytotoxic T lymphocyte-associated antigen 4, E-cadherin, and CD44. RESULTS: Tumors were separated into low (?5) and high tumor budding groups (>5) based on the median budding number. Lymphovascular, perineural invasion, and the number of metastatic lymph nodes were significantly higher in high-grade budding tumors (p=0.001, p<0.001, and p=0.019, respectively). Tumor-infiltrating lymphocytes were significantly higher in tumors without tumor buddings (p[removed]
Keywords: Breast Neoplasms; CD44 Protein; Mouse; CTLA-4 Antigen; E-Cadherin; Tumor Microenvironment